Effect of Tiger Grass (Khaem) Silage on Growth Performance rate and Nutrients Digestibility in Local Yellow Cattle - Chanthakhoun, Vongpasith; Inthaphanya, Sangkom; Kandee , Thanousinh; Tayamath , Khambou (Souphanouvong University Journal Multidisciplinary Research and Development, 2017)
Tiger grass (Khaem), a non-timber forest product (NTFP) is mainly cultivated and propagated because of the economic demand for its flowers which are processed into soft brooms. Khaem as a protein source or green grass in dry season for local yellow cattle and swamp buffaloes has been relatively limited information in Laos. The aim of this study was to determine the Khaem silage as source of fiber and protein for cattle during dry season to improve the feed digestibility and growth rate in “Yellow” local cattle. The 12 local cattle with 101±6 kg live weight were randomly assigned to receive 4 dietary treatments according to a Randomize Completed Block Design. Four treatments were Urea treated rice straw (UTR), Napier Grass Silage (NGS-M), Tiger grass silage + Molasses (TGS-M), Tiger grass silage + Molasses + Urea (TGS-MU) as a roughage was fed ad libitum. All animals were allowed to adapt to feeds respective before samplings were conducted. It was found that the chemical composition of 4 treatments particularly UTR were high of protein than other treatment. Furthermore, the treatments UTR and TGS-M were increased (P<0.05) in terms of total DM intake and ADG. In addition, feed convert ratio (FCR) were significant difference (P<0.05) lowest in TGS-M than other treatments. Based on this experiment, it could be concluded that feed roughage silage, particularly TGS-M was improve the growth performance of local Yellow cattle.